THE MEANING OF ‘BORN FROM ABOVE’ (γεννηθῇ ἄνωθεν) IN JOHN 3: A SEMANTIC ANALYSIS AND ITS IMPLICATIONS FOR THE THEOLOGY OF REGENERATION - Ritwan Imanuel Tarigan; Tanozaro Giawa; Adi Prasetyo Wibowo (CV Naskah Aceh, 2026)
This study examines the semantic meaning of the term γεννηθῇ ἄνωθεν in John 3:3–7 and its implications for the doctrine of regeneration in New Testament theology. The Greek word ἄνωθεν (anōthen) carries significant semantic ambiguity, being translatable either as “from above” or “again.” Through lexical and contextual semantic analysis, this study demonstrates that its usage in the Gospel of John consistently refers to a divine origin, as evidenced in John 3:31, 19:11, and the overall theological framework of the Gospel. Nicodemus’s misunderstanding functions as a deliberate literary device (double entendre) that highlights the contrast between human and divine perspectives. A comparative review of Reformed, Arminian, and Lutheran theological traditions reveals that divergent interpretations of ἄνωθεν directly correlate with differing understandings of the nature of regeneration. The findings affirm that regeneration is a monergistic divine act, not a product of human initiative. These theological implications hold significance for systematic theology, soteriology, and contemporary Christian education.